Pilot Study: Neurocognitive Disorders and Colonoscopy in Older Adults. (September 2019) - Arias, Franchesca; Riverso, Michael; Levy, Shellie-Anne; Armstrong, Rebecca; Estores, David S.; Tighe, Patrick; Price, Catherine C.
Abstract : In a preoperative anesthesia setting with integrated neuropsychology for individuals >64 years of age, we completed a pilot study examining the association between neurocognitive disorders with frequency of missed colonoscopies and quality of bowel preparation (prep). Gastroenterologists completed the Boston Bowel Preparation Scale (BBPS) for each patient. Of 47 older adults seen in our service, 68% met criteria for neurocognitive disorders. All individuals failing to attend the colonoscopy procedure had met criteria for major neurocognitive disorder. Poor bowel prep was also identified in 100% of individuals with major neurocognitive disorder and 28% of individuals with mild neurocognitive disorder. Our pilot data suggest that, in high-risk individuals, the presence of neurocognitive disorders is risk factors for missed appointments and inadequate bowel prep. These pilot data provide reference statistics for future intervention protocols.